2006
DOI: 10.1080/09537100600758867
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma improves expansion of human mesenchymal stem cells and retains differentiation capacity andin vivobone formation in calcium phosphate ceramics

Abstract: The replacement of FCS by PRP eliminated risks connected with the use of xenogeneic supplements. It improved expansion of MSC and retained their differentiation and in vivo bone formation capacity in a setting adaptable to autogenous use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 15 publications
11
113
1
1
Order By: Relevance
“…However, the ''black box'' approach taken by many of the clinicians utilizing PRP leaves much to be done in the realm of basic science to fully understand and standardize the practice. To date, the collection of whole blood and the concentration and isolation of platelets to make PRP has been proven effective in vitro for stimulating cellular activity in a number of formats, both in liquid 13,[33][34][35]37,[39][40][41] and in lyophilized PRGF form. [16][17][18][19] To the best of the authors' knowledge, this article serves as the first instance of a powdered PRGF being incorporated into an electrospun tissue engineering scaffold to serve as a controlled release vehicle for such a concentrated growth factor and cytokine milieu.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the ''black box'' approach taken by many of the clinicians utilizing PRP leaves much to be done in the realm of basic science to fully understand and standardize the practice. To date, the collection of whole blood and the concentration and isolation of platelets to make PRP has been proven effective in vitro for stimulating cellular activity in a number of formats, both in liquid 13,[33][34][35]37,[39][40][41] and in lyophilized PRGF form. [16][17][18][19] To the best of the authors' knowledge, this article serves as the first instance of a powdered PRGF being incorporated into an electrospun tissue engineering scaffold to serve as a controlled release vehicle for such a concentrated growth factor and cytokine milieu.…”
Section: Discussionmentioning
confidence: 99%
“…This was expected, as it had previously been demonstrated that PRGF, as well as growth factors secreted by macrophages, enhanced fibroblast, mesenchymal, and stromal stem cell proliferation. 2,[33][34][35][36][37] In general, ADSC proliferation in all preconditioned medium increased from day 1 to day 4; however, by day 7 it appeared that proliferation slowed, and in some cases cell number even decreased, potentially due to induced contact inhibition as the cells became confluent in the wells, or died off following exhaustion of medium nutrients. This may also have been because the conditioned medium used for the ADSCs was MSFM, which is unfavorable over the long-term for ADSC growth, or due to harmful factors expressed during macrophage apoptosis.…”
Section: Released Prgf Effect On Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…The local environment in the initial fracture hematoma is acidic, which later becomes more alkaline as the healing progress [1]. Platelet-rich plasma and platelet derivates contain several potent growth factors and have, therefore, been used for growth stimulation of a variety of mesenchymal cells [2][3][4][5]. Platelet preparations have also been used clinically to stimulate bone formation and wound healing [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…19 Cell density is a critical factor affecting the growth of cells. Culture attempts are usually unsuccessful below a critical cell density.…”
Section: Introductionmentioning
confidence: 99%